A Hollow NaGdF4/AFn Nanosystem Based on "Relay Race" Release for Therapy. (25th July 2017) - Zhou, Jie; Yao, Hanchun; Meng, Lingchang; Sun, Chong; Ye, Weiran; Du, Qiuzheng
Abstract: To develop a multifunctional nanomaterial for dual‐mode imaging and synergetic chemotherapy, curcumin (CUR) was physically entrapped into hollow upconversion NaGdF4 nanomaterial, then apoferritin (AFn) loaded with doxorubicin (DOX) was attached to the NaGdF4 surface. Subsequent modification with the targeting reagent folic acid (FA) led to generation of the CUR/NaGdF4 –DOX/AFn–FA conjugate for cancer treatment. X‐ray diffraction, scanning (SEM) and transmission electron microscopy (TEM), and Fourier transform infrared (FTIR) spectroscopy demonstrated the successful preparation of hexagonal‐phase NaGdF4 and NaGdF4 –AFn–FA. Moreover, no toxicity was observed for NaGdF4 –AFn–FA. In vitro and in vivo experiments demonstrated that the two drugs are sequentially released from the nanocomposites. This two‐drug system showed strong growth inhibitory effects on MCF‐7 cells. Upconversion luminescence imaging and magnetic resonance (MR) imaging of NaGdF4 –AFn–FA were carried out. The results of this study show that NaGdF4 –AFn–FA can be used for targeted anticancer drug delivery as well as imaging, a novel multi‐pronged theranostic system for tumor treatment. Abstract : Pass the baton ! We synthesized hollow mesoporous structured NaGdF4 nanoparticles with both excellent upconversion luminescent and magnetic resonance capacities for in vivo imaging applications. The dual‐drug system CUR/NaGdF4 –DOX/AFn–FA enabled the temporal release of two drugs: curcumin (CUR) is released rapidly to inhibit P‐glycoprotein (P‐gp) activity and to restore apoptosis signaling pathways, while doxorubicin (DOX) undergoes sustained release and thus high accumulation in drug‐resistant cells to exert its therapeutic effect thanks to CUR‐mediated inactivation of P‐gp.